Dielectronic Recombination in He-like, Li-like and Be-like Bismuth and KLM Resonances - YAVUZ, İLHAN (IOP PUBLISHING LTD, 2012)
DR rate coefficients for He-like, Li-like and Be-like Bismuth ions and KLM resonances are calculated using MCBP approximation.